Kindlin-1 Regulates Astrocyte Activation and Pain Sensitivity in Rats With Neuropathic Pain. Issue 5 (July 2018) - Zhao, Baisong; Pan, Yongying; Xu, Haiping; Song, Xingrong
Abstract : Background and Objectives: Astrocyte activation has been implicated in the pathogenesis of neuropathic pain, but the involvement of kindlin-1 in astrocyte activation and neuropathic pain has not yet been illustrated. Using a chronic constriction injury (CCI) rat model of neuropathic pain, we investigated the expression levels of kindlin-1 during neuropathic pain and the influences of kindlin-1 on regulating pain sensitivity. Methods: Neuropathic pain was induced in rats by CCI of the sciatic nerve. Rats were randomly assigned to 4 groups: sham operation, CCI, CCI + kindlin-1 short hairpin RNA (shRNA), and CCI + kindlin-1 groups. Animals in the CCI + kindling-1 shRNA and CCI + kindlin-1 groups were given kindlin-1 shRNA or kindlin-1 virus infection to reduce or overexpress kindlin-1, respectively. Kindlin-1 expression was persistently increased in rats 10 days after CCI. A large proportion of glial fibrillary acidic protein (GFAP)–positive astrocytes expressed kindlin-1 in spinal cord tissues of rats after CCI. Results: Compared with the sham operation group, CCI animals exhibited increased GFAP expression and GFAP-positive astrocytes in the spinal cord. Down-regulation of kindlin-1 reduced the up-regulation of GFAP in the spinal cord, whereas overexpression of kindlin-1 promoted elevation of GFAP levels. Kindlin-1 silencing elevated the mechanical and thermal pain thresholds of CCI rats ( P < 0.05). However, overexpression of kindlin-1 aggravated CCI-induced pain sensitivity. Conclusions: Kindlin-1 may regulate pain sensitivity by affecting activated astrocytes in the spinal cord. Inhibition of kindlin-1 may provide a novel paradigm for the management of neuropathic pain. Abstract : Supplemental digital content is available in the text.